Studi Fenomenologi Pengalaman Keluarga Dalam Merawat Lansia Dengan (DM) Diabetes Mellitus - Sofwan Sofwan (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
This research aims to gain an in-depth understanding of the meaning and importance of family experiences in caring for elderly people with diabetes in the city of Depok. This research uses a qualitative descriptive phenomenology method combined with in-depth interview methods. Participants in this study were the primary caregivers of elderly adults with diabetes who were collected using the criteria examining technique. Information collected in the form of audio recordings of interviews and field notes was analyzed using the Collaizi technique. This research identified 13 themes, namely changes in the elderly, ability to complete family health tasks, psychological responses, physical responses, economic responses, role responses, problem solving behavior, problem solving support, ideal life in the elderly. Capacity for services for the elderly, natural services, forms of service and respect for religious and cultural teachings.